1999
DOI: 10.1074/jbc.274.17.12108
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the 5′-Flanking Region of the Human Growth Hormone-releasing Hormone Receptor Gene

Abstract: We cloned the 5-flanking region of the human growth hormone-releasing hormone receptor (GHRH-R) gene and determined the nucleotide sequence of 2.7 kilobases upstream from the translation start site. RNase protection analysis showed the major transcription start site is 122 base pairs upstream from the translation start site. The 5-end of the longest product of 5-rapid amplification of cDNA ends was close to the site. There were no typical TATA homologies but several putative regulatory elements including Pit-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
(26 reference statements)
1
36
1
Order By: Relevance
“…2 that the transcription from dGpG with no pit-1 site responded to DEX by 4·4-fold (Fig. 2), while it coincides well with previous results that showed that the transcription of the GHRH-receptor gene requires pit-1 (Lin et al 1992, Iguchi et al 1999, Miller et al 1999, Nogami et al 2002. The only explanation possible for this discrepancy is that some DNA sequences within dGpG-p that are absent in dGpG, the pit-1 site and the 14-base pair spacer between pGRE and the pit-1 site, contain the silencer element.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…2 that the transcription from dGpG with no pit-1 site responded to DEX by 4·4-fold (Fig. 2), while it coincides well with previous results that showed that the transcription of the GHRH-receptor gene requires pit-1 (Lin et al 1992, Iguchi et al 1999, Miller et al 1999, Nogami et al 2002. The only explanation possible for this discrepancy is that some DNA sequences within dGpG-p that are absent in dGpG, the pit-1 site and the 14-base pair spacer between pGRE and the pit-1 site, contain the silencer element.…”
Section: Resultssupporting
confidence: 79%
“…The PCR fragment obtained by primer A and one of these was placed upstream of the tk promoter to generate dGpGmp or dGpG-pm respectively. Similarly, the primers carrying pit-1 sequences of the rat GH gene (rGH-2, Andersen & Rosenfeld 1994, 5 -CTGATGG ATAATTTAAAGGATGGTGGGACATT-3 ), the rat prolactin gene (rPrl-1P, Andersen & Rosenfeld 1994, 5 -CATGAATATATATATAAATGGTGGGACATT-3 ) and the human GHRH-receptor gene (hGHRHR-P2, Iguchi et al 1999, 5 -CGCTGAATATTCACCAGGAT GGTGGGACATT-3 ) were used to generate dGpGGHp, dGpG-PRLp and dGpG-hGHRHRp respectively (see Fig. 6).…”
Section: Plasmid Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear correspondence between exons of the gene and functional domains of the receptor protein. Functional analysis of the gene promoter in cell transfection assays reveals a selective preference for expression in pituitary cells (Iguchi et al, 1999;Miller et al, 1999) likely due to the presence of the transcription factor Pit-1, which positively regulates GHRH receptor gene expression (Lin et al, 1992;Iguchi et al, 1999;Miller et al, 1999;Salvatori et al, 2002). Glucocorticoid regulation has also been mapped to a composite regula- FIG.…”
Section: F the Growth Hormone-releasing Hormone Receptor Gene And Rementioning
confidence: 99%
“…It is involved in the development of the three pituitary cell types, somatotrophs, lactotrophs, and thyrotrophs, as well as the gene expression of growth hormone (GH), 1 prolactin (PRL), GH-releasing hormone receptor (GHRH-R), thyrotropin ␤ subunit (TSH ␤), and Pit-1 itself by binding to the specific DNA elements of these genes (3)(4)(5)(6)(7)(8)(9)(10). Therefore, abnormalities of the Pit-1 gene result in GH, PRL, and TSH deficiencies.…”
mentioning
confidence: 99%